Preliminary Silvicultural Techniques for Planning of Shrubs in the Siwaliks and Himalayas for Rehabilitation of Wastelands and Degraded Sites - Maithani, G. P.; Bahuguna, V. K.; Thapliyal, R. C. (Indian Forester, 1989)
The importance of shrubs in reclaiming the eroded slopes of Himalayas and Siwaliks has been discussed. Since it is being increasingly felt that in such barren and degraded areas before planting trees shrubs should be encouraged to grow to retain soil moisture and to improve the site conditions. The growing techniques of most of the shrubs species have not been studied before in India. The Silviculture Division of this Institute for the past few years has done some prliminary work on the silvicultural aspects such as nursery and planting techniques and seed processing and germination. The paper presents a review of such work done in the division in the recent past.